2020
DOI: 10.1080/03639045.2020.1788061
|View full text |Cite
|
Sign up to set email alerts
|

Development of orally administered insulin-loaded polymeric-oligonucleotide nanoparticles: statistical optimization and physicochemical characterization

Abstract: Introduction: Therapeutic peptides are administered via parenteral route due to poor absorption in the gastrointestinal (GI) tract, instability in gastric acid and GI enzymes. Polymeric drug delivery systems have achieved significant interest in pharmaceutical research due to its feasibility in protecting proteins, tissue targeting and controlled drug release pattern. Materials and Methods:In the present study, the size, polydispersity index and zeta potential of insulin-loaded nanoparticles were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…As chitosan has various beneficial effects on human health, for instance, in bone healing [ 48 , 49 ], it makes it quite an ideal biomaterial to employ in the drug delivery research sector. Various labs, including ours [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], have shown that chitosan is capable of encapsulating various types of therapeutic agents such as small molecule drugs to exploratory biologicals such as proteins and even DNA in delivery platforms of various sizes. As chitosan can even be ingested with no complications, this fact further cements the usefulness of this biopolymer in drug delivery R&D. Chitosan NPs have been formulated in the past using various methods, not limited to complex coacervation [ 64 ] and ionotropic gelation [ 65 ], both simple enough to carry out in most labs.…”
Section: Chitosan—a Promising Biopolymer That Has Potential In Athero...mentioning
confidence: 99%
See 1 more Smart Citation
“…As chitosan has various beneficial effects on human health, for instance, in bone healing [ 48 , 49 ], it makes it quite an ideal biomaterial to employ in the drug delivery research sector. Various labs, including ours [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], have shown that chitosan is capable of encapsulating various types of therapeutic agents such as small molecule drugs to exploratory biologicals such as proteins and even DNA in delivery platforms of various sizes. As chitosan can even be ingested with no complications, this fact further cements the usefulness of this biopolymer in drug delivery R&D. Chitosan NPs have been formulated in the past using various methods, not limited to complex coacervation [ 64 ] and ionotropic gelation [ 65 ], both simple enough to carry out in most labs.…”
Section: Chitosan—a Promising Biopolymer That Has Potential In Athero...mentioning
confidence: 99%
“…HGC NPs are biodegradable, have low immunogenicity and are adaptable to carry a variety of therapeutic agents in vivo [ 69 , 70 ]. Depending on the formulation technique used, this biopolymer can be relatively inexpensive and easy to use, as we [ 60 , 61 , 62 , 71 , 72 , 73 ] and others [ 74 , 75 ] have established previously. We now review the collection of articles in the literature that have used chitosan-based NPs in atherosclerosis research (none has yet been tested clinically, so the discussions revolve around cell culture and preclinical animal models testing)—that is, tested as a diagnostic, therapeutic or both diagnostic and therapeutic (theranostic) platform.…”
Section: Chitosan Nanoparticles Used In Atherosclerosis Researchmentioning
confidence: 99%
“…[43,205,216,217] Nanoparticles possess several favourable properties, including stability against enzymatic degradation, improved bioavailability and high carrier capacity. [218][219][220][221] One of the studies examined the antidiabetic effects of bioflavonoids-loaded nanoparticles on C2C12 cells and streptozotocin-induced diabetic rat model. [121] It was found that nanoparticles containing myricitrin (1, 3, and 10 mg/kg) could increase glycogen synthesis and its storage, GLUT-4 gene expression, glucose uptake and cell viability in C2C12 cells.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…An alternative approach is the use of nanoparticles. Although confirmation in the clinical setting is still required, such nanoparticulated drugs (nanodrugs) have recently gained recognition in drug delivery for a number of therapeutic areas [ 118 , 119 , 120 ]. Indeed, Geiger et al showed that nanoparticles carrying IGF-1 successfully penetrated bovine cartilage within 2 days of application [ 121 ].…”
Section: Optimisation Of Oligonucleotide Methods Of Delivery Into Joint Tissuesmentioning
confidence: 99%